Pelatihan Diversifikasi Produk Ikan Tuna untuk meningkatkan Kreativitas Masyarakat di Desa Kolorai Kecamatan Morotai Selatan Kabupaten Pulau Morotai - Septiana Sulistiawati; Rinto M Nur; Iswandi Wahab; Titien Sofiati; Djainudin Alwi; Kismanto Koroy; Nurafni Nurafni; Sandra Hi Muhammad; Asy’ari Asy’ari (Journal Of Khairun Community Services, 2021)
The meat of tuna, cobs, cakalang are raw materials that can be processed into food products such as meatballs, nuggets, sausages, and other processed. Surimi is used as an intermediate material in the processing diversification of products from dark red fleshy fish commodities such as tuna, cobs, and cakalang. Community service activities were held in June 2021 at Kolorai Village Hall of South Morotai District of Morotai Island Regency. The implementation of devotional activities through 3 stages includes preparation, socialization, and training—community service activities in the form of training in processing diversification of tuna products. The training begins with socialization aimed at transferring knowledge to participants about principles, procedures, materials, equipment, and factors that affect the processing of fishery products. The core activities of this equipment are carried out in the form of direct training in the form of practice of making nugget products, dragon legs, and empek-empek. Together with the team, the speaker introduces and explains the ingredients used in the manufacture of the product. Then start making the product in order from processed fish into nuggets, dragon legs, and chips. This activity lasts for 1x24 hours and ends with the provision of parcels of processing materials for trainees.